Future directions for the discovery of natural product-derived immunomodulating drugs: an IUPHAR positional review. (March 2022) - Wainwright, Cherry L.; Teixeira, Mauro M.; Adelson, David L.; Braga, Fernão C.; Buenz, Eric J.; Campana, Priscilla R.V.; David, Bruno; Glaser, Keith B.; Harata-Lee, Yuka; Howes, Melanie-Jayne R.; Izzo, Angelo A.; Maffia, Pasquale; et al.
Abstract: Drug discovery from natural sources is going through a renaissance, having spent many decades in the shadow of synthetic molecule drug discovery, despite the fact that natural product-derived compounds occupy a much greater chemical space than those created through synthetic chemistry methods. With this new era comes new possibilities, not least the novel targets that have emerged in recent times and the development of state-of-the-art technologies that can be applied to drug discovery from natural sources. Although progress has been made with some immunomodulating drugs, there remains a pressing need for new agents that can be used to treat the wide variety of conditions that arise from disruption, or over-activation, of the immune system; natural products may therefore be key in filling this gap. Recognising that, at present, there is no authoritative article that details the current state-of-the-art of the immunomodulatory activity of natural products, this in-depth review has arisen from a joint effort between the International Union of Basic and Clinical Pharmacology (IUPHAR) Natural Products and Immunopharmacology Sections, with contributions from a number of world-leading researchers in the field of natural product drug discovery, to provide a "position statement" on what natural products has to offer in the search for new immunomodulatory argents. To this end, we provide a historical look at previous discoveries of naturally occurring immunomodulators, present a picture of the current status of the field and provide insight into the future opportunities and challenges for the discovery of new drugs to treat immune-related diseases.